PERAN TATA KELOLA DAN PENGENDALIAN INTERNAL DALAM MENCEGAH KECURANGAN PADA LEMBAGA PERKREDITAN DESA SE-KECAMATAN MENGWI - Ni Luh Ayu Puspita Dewi; A.A. Krisna Murti; I Dewa Ayu Kristiantari (Program Studi Akuntansi, Fakultas Ekonomi, Universitas Warmadewa, 2025)
This lesson aims to analyze each factor that is used as the theme of discussion of this lesson material. This lesson was held at the Village Credit office in Mengwi District. To determine the sample using non-probability sampling with a saturated method, a total of 36 participants were found. To collect the data by distributing questionnaires, then analyzing it from non-parametric. The lesson resulted in management having an optimal relationship to handling fraud, so that personal control shows an optimal relationship to handling fraud.